Gamification of dermatoscopy education using a smartphone mobile platform: A pilot studyCapsule Summary - Shashendra Aponso, MD, MRCP; Yue Ting Nichole Tan, BSc (Pharm); Siddharth Jain, BCom; Choon Chiat Oh, MBBS, MSc (Elsevier, 2024)
Background: Dermatoscopy is a noninvasive method of examining skin lesions under high magnification, gradually replacing the need for invasive biopsies. Training is required to gain clinical competency. Gamification employs game-like elements to enhance education engagement and is an engaging means of delivering medical education. We sought to use gamification and a mobile-based platform to deliver dermatoscopy education to physicians. Methods: We developed SKIN@GoPRIME, an interactive smartphone platform. Thirty physician participants were randomly assigned to watch an online dermatoscopy lecture or to use SKIN@GoPRIME. Twenty-eight participants completed prelearning and postlearning quizzes and provided feedback on SKIN@GoPRIME. Results: Users of SKIN@GoPRIME demonstrated a significant 1.71-point mean score improvement (P = .0018). The group that watched the online dermatoscopy lecture had a higher 2.36-point mean score improvement (P = .00021). Both family medicine and internal medicine physicians demonstrated a significant mean score increase of 1.29 (P = .049) and 2.14 (P = .023), respectively, after using SKIN@GoPRIME. Based on feedback, 83% believed that SKIN@GoPRIME can be used to acquire the applied competencies required for their job scope. Discussion and Conclusion: SKIN@GoPRIME, a novel learning tool via gamification effectively delivers dermatoscopy education, although it is not shown to be more effective than lectures. Larger studies are required to further validate the effectiveness of gamified learning techniques in dermatoscopy education. Future studies should involve the optimization of SKIN@GoPRIME to more effectively deliver dermatoscopy education.